2022
DOI: 10.1111/ctr.14771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the presence of median arcuate ligament on biliary complications after liver transplantation

Abstract: Introduction The presence of median arcuate ligament (MAL) during orthotopic liver transplantation (OLT) may cause a significant reduction in the arterial hepatic flow. The aim of the present study is to investigate the impact of MAL on biliary complications in patients who underwent OLT. Methods We performed a retrospective case‐control study among patients who underwent OLT in Geneva University Hospital between 2007 and 2017, depending on the presence or absence of MAL. The matching was performed according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Gialamas et al demonstrated no statistically significant difference in graft survival or post-operative biliary complications between patients with and without MALS in their retrospective case-control study [30]. They concluded that if the arterial flow to the graft is adequately established, the choice of treating MALS might not influence the overall outcome and development of complications [30]. Another single-center European study also showed no differences in short-and long-term outcomes between OLT patients with surgically treated MALS or without MALS [31].…”
Section: Significance Of Median Arcuate Ligament Syndrome In Hepato-p...mentioning
confidence: 83%
See 2 more Smart Citations
“…Gialamas et al demonstrated no statistically significant difference in graft survival or post-operative biliary complications between patients with and without MALS in their retrospective case-control study [30]. They concluded that if the arterial flow to the graft is adequately established, the choice of treating MALS might not influence the overall outcome and development of complications [30]. Another single-center European study also showed no differences in short-and long-term outcomes between OLT patients with surgically treated MALS or without MALS [31].…”
Section: Significance Of Median Arcuate Ligament Syndrome In Hepato-p...mentioning
confidence: 83%
“…Reduced blood flow predisposes the graft to hepatic arterial thrombosis, a dreadful complication that can lead to cholangitis, poor graft function, graft loss, and death [29]. The prevalence of MALS during OLT is reported to be up to 10%, and contemporary well-powered studies on its management are scarce in the literature [30][31][32][33]. Gialamas et al demonstrated no statistically significant difference in graft survival or post-operative biliary complications between patients with and without MALS in their retrospective case-control study [30].…”
Section: Significance Of Median Arcuate Ligament Syndrome In Hepato-p...mentioning
confidence: 99%
See 1 more Smart Citation